Pengembangan E-booklet Ragam Tanaman Obat di Banten Pada Materi Klasifikasi Makhluk Hidup Untuk Menumbuhkan Minat Belajar Peserta Didik SMP Kelas VII - Zahra, Nabila Latipa; Kurniasih, Septi; Suryani, Dwi Indah (PendIPA Journal of Science Education, 2026)
Low interest in learning is a common problem in the learning process. The cause is the limited teaching materials available in schools. This condition results in suboptimal understanding of the material and decreased student engagement during learning activities. Based on these problems, an e-booklet teaching material was developed to support the learning interest of seventh-grade junior high school students. The purpose of this study was to measure the validity and response of students to teaching materials in the form of e-booklets discussing medicinal plants in the Banten region. The method applied in this study was Research and Development (R&D) using the ADDIE model, which consists of four stages, namely analysis, design, development, and implementation. The research instruments consisted of expert validation sheets and questionnaires to measure student responses, which had undergone a validation process by instrument experts using the judgment method. The data obtained were analyzed using descriptive qualitative and quantitative approaches. The results showed that the e-booklet achieved a validity level of “Highly Valid” with an average percentage of 87.84%, based on validation from subject matter experts, teaching material experts, and practitioner experts who were junior high school science teachers. After undergoing a revision process, the product was tested on a limited basis with students and received a response rate of 97.79%, which falls into the “Very Good” category. Thus, the e-booklet is declared suitable for use as teaching material.